A simple ear splint for microtia patients - C J Venkata Krishnan; S M Balaji; Ashish R Jain (Wolters Kluwer Medknow Publications, 2015)
Microtia is a congenital anomaly of the ear can occur as an isolated birth defect or as part of a spectrum of anomalies or as a syndrome. Microtia is often associated with impaired hearing and or total loss of hearing. Such patients typically require treatment for surgical ear reconstruction and for hearing impairment. Maintenance of ear projection and post auricular sulcus in staged ear reconstruction in microtia is a trying problem. So also is the maintenance of the patency of the external auditory meatus following recanalization and meatoplasty.This case report describes a simple effective way of fabrication of ear splint prosthesis.